Criminal justice in a small Nordic country: The case of Iceland - Gunnlaugsson, Helgi (Dansk Kriminalistforening, 2021)
AbstractCrime concerns have deepened in Iceland in the new millennium. The number of criminal court decisions increased until 2013, when it temporarily levelled off before reaching a new peak in 2019. This development has put pressure on the prison system, as a long list of convicts awaiting completion of their sentences has accumulated. This paper uses official data, previous research and media accounts to examine the response of Icelandic authorities to this trend. One of the main questions addressed in the article is whether the criminal policy adopted by Icelandic authorities suggests a movement toward punitive or non-custodial measures. As it turns out, the Icelandic prison system has undergone major changes to meet this penal challenge. A new modern prison has recently been built close to Reykjavík to replace three smaller, older facilities that have beenclosed. This suggests a punitive turn. Yet at the same time, non-custodial sanctions have been increasingly introduced and implemented in lieu of sentences to closed security prisons. These non-custodial sanctions include electronic surveillance, additional community service work and an increased possibility to serve time in open prison units. It is contended here that a combination of practical budget concerns and rehabilitation sentiments lies behind this criminal policy development.AbstractKriminaliteten i Island har skabt voksende bekymringer i det nye årtusind. Antallet af strafferetlige afgørelser var stigende indtil 2013, hvor det fladede ud for en tid. Men i 2019 nåede antallet nye højder. Denne tendens har skabt et pres inden for fængselssystemet, der bl.a. viser sig i ophobning af domfældte, der må vente på at afsone deres dom. I denne artikel undersøges de islandske myndigheders reaktion på denne udvikling på baggrund af officielle data, tidligere forskning og mediernes dækning. Et af de mange spørgsmål, der bliver stillet i denne artikel, går ud på hvorvidt den islandske kriminalpolitik går i retning af mere eller mindre indespærring. Det islandske fængselssystem har gennemgået gennemgribende ændringer. Et moderne fængsel er for nylig blevet opført i umiddelbar nærhed af Reykjavik, hvilket ville antyde en straffende tendens, mens tre mindre og ældre fængselsinstitutioner er blevet lukket. Samtidigt har myndighederne i stigende grad anvendt ikke-frihedsberøvende straffe som alternativ til de lukkede fængsler. Blandt de nye metoder er elektronisk overvågning, mere samfundstjeneste og øgede muligheder for afsoning i åbne fængsler. Artiklen vil vise, at såvel budget- som resocialiseringshensyn står bag denne udvikling i straffepolitikken. Artiklens danske titel er: Straf i et lille nordisk land: Tilfældet Island.